2021
DOI: 10.1039/d1dt00322d
|View full text |Cite
|
Sign up to set email alerts
|

Four new Cu6S6 cluster-based coordination compounds: synthesis, crystal structures and fluorescence properties

Abstract: The hexagonal prismatic Cu6S6 cluster exhibits excellent near-infrared fluorescence properties due to its short Cu-Cu bonds, however, the construction of Cu6S6 cluster-based compounds with extended structure is still a challenge....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…In the Fourier transform infrared (FTIR) spectra (Additional le 1: Figure S2), the adsorption peaks of S-H stretch were absent in the spectra of Cu 6 NC and the C = C/C = N peaks were apparently red-shifted, suggesting the formation of the coordination between mercaptopyrimidine and Cu ions. [42] Such coordinated ligands led to considerable thermal stabilities. Under nitrogen atmosphere, the thermogravimetric analysis (TGA) revealed that Cu 6 NC could be maintained from room temperature to nearly 400 ℃ and the total weight loss of Cu 6 NC achieved ~ 50 % at 800 ℃ (Additional le 1: Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…In the Fourier transform infrared (FTIR) spectra (Additional le 1: Figure S2), the adsorption peaks of S-H stretch were absent in the spectra of Cu 6 NC and the C = C/C = N peaks were apparently red-shifted, suggesting the formation of the coordination between mercaptopyrimidine and Cu ions. [42] Such coordinated ligands led to considerable thermal stabilities. Under nitrogen atmosphere, the thermogravimetric analysis (TGA) revealed that Cu 6 NC could be maintained from room temperature to nearly 400 ℃ and the total weight loss of Cu 6 NC achieved ~ 50 % at 800 ℃ (Additional le 1: Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…S25 †), indicating that fluorescence quenching is not caused by energy competition absorption. 45,76 Thirdly, the Förster resonance energy transfer (FRET) mechanism state that the luminescence quenching behavior is related to the degree of spectral overlap between donor emission and acceptor absorption, [77][78][79] however, no overlap between the emission spectrum of compound 1 (from 580 to 720 nm) and absorption spectra of organic amine ethanol solution (below 320 nm) is observed (Fig. S26 †), and therefore, the FRET mechanism is ruled out.…”
Section: Fluorescence Quenching Mechanism To Organic Aminesmentioning
confidence: 99%
“…[34][35][36] Fluorescent metalorganic frameworks (MOFs) are an important member of the sensing material family due to their long fluorescence lifetime, high quantum yield, sensitive response to the surrounding environment, low cost and simple detection process. Recently, many fluorescent MOFs were reported for the detection of anions, [37][38][39] cations [40][41][42] and nitro compounds, [43][44][45] , however, the rational design and synthesis of target MOFs with functional sites for specific host-guest recognition and thus to detect organic amines are very limited. Guo Z. Y. et al reported a ketone functionalized luminescent terbium MOF which can be realized for the highly selective and sensitive sensing of aniline.…”
Section: Introductionmentioning
confidence: 99%
“… 11 18 Among them, hexacopper(I) clusters formulated as [Cu 6 S 6 ], constitute a rarely explored family of polynuclear complexes, with high potential in the design of NIR luminescent materials. 19 23 …”
Section: Introductionmentioning
confidence: 99%
“…Solid materials and coordination compounds emitting in the near-infrared (NIR) have emerged as promising and challenging materials with potential applications in optoelectronics, sensors, and telecommunications. Cu­(I) compounds are a special class of materials for their remarkable photophysical and electronic properties. In particular, polynuclear Cu­(I) clusters are an intriguing family of materials that are being investigated for promising applications in optoelectronics and luminescence signaling. Among them, hexacopper­(I) clusters formulated as [Cu 6 S 6 ], constitute a rarely explored family of polynuclear complexes, with high potential in the design of NIR luminescent materials. …”
Section: Introductionmentioning
confidence: 99%